Inflammation and Alzheimer's Disease: Mechanisms and Therapeutic Implications by Natural Products - Mashoque Ahmad Rather; Andleeb Khan; Saeed Alshahrani; Hina Rashid; Marwa Qadri; Summya Rashid; Rana M. Alsaffar; Mohammad Amjad Kamal; Muneeb U. Rehman (Hindawi Limited, 2021)
Alzheimer's disease (AD) is a neurodegenerative disorder with no clear causative event making the disease difficult to diagnose and treat. The pathological hallmarks of AD include amyloid plaques, neurofibrillary tangles, and widespread neuronal loss. Amyloid-beta has been extensively studied and targeted to develop an effective disease-modifying therapy, but the success rate in clinical practice is minimal. Recently, neuroinflammation has been focused on as the event in AD progression to be targeted for therapies. Various mechanistic pathways including cytokines and chemokines, complement system, oxidative stress, and cyclooxygenase pathways are linked to neuroinflammation in the AD brain. Many cells including microglia, astrocytes, and oligodendrocytes work together to protect the brain from injury. This review is focused to better understand the AD inflammatory and immunoregulatory processes to develop novel anti-inflammatory drugs to slow down the progression of AD.